Półka literacka 2014 - Nęcka, Agnieszka (Postscriptum Polonistyczne, 2020)
The article presents both the most important and interesting prose and poetry publications that appeared in 2014. Last year was marked by the dominance of the wellknown authors (such as Justyna Bargielska, Jacek Dehnel, Ignacy Karpowicz, Olga Tokarczuk, Mariusz Sieniewicz, Agnieszka WolnyHamkało, Piotr Szewc, Agnieszka Mirahina, Magdalena Tulli, Zbigniew Kruszyński) and proved that books that deal with identity problems and cast heroes who are facing the demons of the past can gain positive readers‘ responses.